EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (Student Team Achievement Divission) DENGAN MENGGUNAKAN ALAT PERAGA LIPON PADA PEMBELAJARAN MATERI OPERASI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT DI KELAS V SDN BALUN 2 TURI LAMONGAN TAHUN PELAJARAN 2014-2015 - Rusmining, -; Rizkiahwati, Devi (saintis, 2016)
To improve the quality of education, teachers were required to master the material and learning strategies that originally centered on the teacher becomes a student-centered. The implementation of cooperative learning model type STAD with props LIPON on material operations of addition and subtraction of integer in class V SDN Balun 2 Turi Lamongan in the academic year of 2014-2015 could assist students in improving their academic achievement. The purpose of this study was to describe the level of completeness of student learning, student activities, teacher activities, and student responses on the implementation of cooperative learning model type STAD with props LIPON on learning the material operations of addition and subtraction of integer. This research was conducted in SDN Balun 2 Turi Lamongan with research subjects were students of class V SDN Balun 2 Turi Lamongan as many as 24 students. Instruments used include about posttest, observation sheet student activities, teacher activity observation sheet, and a student questionnaire responses. Based on the results obtained during the four meetings that the enforceability of the implementation of cooperative learning model type STAD with props LIPON on material operations of addition and subtraction of integers declared effectively applied. Categorized effectively applied for has been reviewed on several things, including: (1) the percentage of students in classical learning completeness declared complete by 91.67%. (2) the activity of students during the learning takes place was seen through observation of student activity sheets declared effective applied with positive activity of 96.56% and negative activity was 3.44%. (3) the teachers activities during the learning takes place was seen through observation of student activity sheets declared effective applied with positive activities amounted to 97.50% and 2.50% negative activity. (4) The students response amounted to 97.50% and 2.50% responded positively respond negatively.